2020
DOI: 10.3847/1538-4357/ab7758
|View full text |Cite
|
Sign up to set email alerts
|

Wide-field Survey of Dwarf Satellite Systems around 10 Hosts in the Local Volume

Abstract: We present the results of an extensive search for dwarf satellite galaxies around 10 primary host galaxies in the Local Volume (D<12 Mpc) using archival CFHT/MegaCam imaging data. The hosts span a wide range in properties, with stellar masses ranging from that of the LMC to ∼3 times that of the Milky Way (MW). The surveyed hosts are: NGC 1023, NGC 1156, NGC 2903, NGC 4258, NGC 4565, NGC 4631, NGC 5023, M51, M64, and M104. We detect satellite candidates using a consistent semi-automated detection algorithm that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
155
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(164 citation statements)
references
References 170 publications
(186 reference statements)
9
155
0
Order By: Relevance
“…Regarding this aspect, it is interesting that a recent Hubble Space Telescope study of low-mass spiral galaxies at redshifts 0.1 to 0.8 finds good agreement between the observed luminosity function down to M V = −15 mag and the predicted abundance of satellites (Roberts et al 2020). Furthermore, Carlsten et al (2020) finds that the abundance of satellites of more massive Local Volume galaxies is in good agreement between the observed and expected number of satellites. This is compatible with our earlier assessment of the Cen A group, where we found that the luminosity function matches the prediction within the 90% confidence interval (Müller et al 2019b).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Regarding this aspect, it is interesting that a recent Hubble Space Telescope study of low-mass spiral galaxies at redshifts 0.1 to 0.8 finds good agreement between the observed luminosity function down to M V = −15 mag and the predicted abundance of satellites (Roberts et al 2020). Furthermore, Carlsten et al (2020) finds that the abundance of satellites of more massive Local Volume galaxies is in good agreement between the observed and expected number of satellites. This is compatible with our earlier assessment of the Cen A group, where we found that the luminosity function matches the prediction within the 90% confidence interval (Müller et al 2019b).…”
Section: Discussionsupporting
confidence: 63%
“…The Local Volume (D < 11 Mpc, Kraan-Korteweg & Tammann 1979;Karachentsev et al 2004Karachentsev et al , 2013 hosts over 30 large galaxies with total luminosities in excess of M tot ≈ −20 K mag. Several surveys have targeted the more prominent of these giant galaxies like M 83 (Müller et al 2015), Centaurus A (Crnojević et al 2014(Crnojević et al , 2016Müller et al 2017;Taylor et al 2018), and others (Merritt et al 2014;Karachentsev et al 2015;Javanmardi et al 2016;Park et al 2017;Smercina et al 2018;Bennet et al 2019;Carlsten et al 2020;Davis et al 2020). Furthermore, dwarf galaxy surveys reach even more distant galaxy clusters (Venhola et al 2017;Wittmann et al 2019), groups (Geha et al 2017;Cohen et al 2018;Habas et al 2020), and the field (Greco et al 2018;Prole et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To what extent the Milky Way is actually representative of disc galaxies is presently uncertain, though. With the advent of new deep, dedicated extragalactic surveys of so-called "Milky Way analogues" (i.e., disc galaxies with total halo masses of ≈ 10 12 M ⊙ ) in the Local Volume (Danieli et al 2017;Smercina et al 2018;Bennet et al 2019;Crnojević et al 2019;Bennet et al 2020;Carlsten et al 2020b) and out to ∼ 40 Mpc (Geha et al 2017;Mao et al 2020), there is a rapidly diminishing requirement to rely on the Milky Way as our template for disc galaxy formation. Instead, the rapid increase in the number of Milky Way-mass galaxies with high-quality data available, both in observations and in cosmological simulations, motivates a reassessment of what constitutes a typical disc galaxy and how the Milky Way fits into this picture.…”
Section: Introductionmentioning
confidence: 99%
“…Observationally, searches for the satellite populations around nearby MW analogs were pioneered by Zaritsky et al (1993Zaritsky et al ( , 1997 and are now being pursued by various groups (e.g., Crnojević et al 2016;Javanmardi et al 2016;Bennet et al 2019;Carlsten et al 2020). One of the most extensive of these campaigns is the ongoing Satellites Around Galactic Analogs (SAGA; Geha et al 2017) survey, which aims to detect and characterize all satellites brighter than the Leo I dwarf (M * ∼ 10 6.6 M e ) around 100 MW-like hosts.…”
Section: Introductionmentioning
confidence: 99%